STUDI SURVEI KEPUASAN PASIEN: PERAN PELAYANAN KEFARMASIAN DI PUSKESMAS AIR DINGIN DALAM MENINGKATKAN KUALITAS LAYANAN KESEHATAN - Elvionita, Cindy; Marsellinda, Elsa (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2024)
Puskesmas (Community Health Center) is one of the primary health facilities that is the front line in providing health services to the community. One of the important pillars in improving the quality of health services in the Community Health Center is pharmaceutical services. The intended pharmaceutical services include the provision of drugs, information on drug use, and counseling to patients. Patient satisfaction is an important indicator used in evaluating the quality of health services. This study aims to determine the level of satisfaction felt by patients with pharmaceutical services and evaluate pharmaceutical services at the Air Dingin Community Health Center as a form of improving the quality of health services. This study used a quantitative survey conducted cross-sectionally in September 2024 at the Air Dingin Community Health Center in Padang City with 45 respondents. This study obtained results, namely the level of patient satisfaction in the reliability aspect of 82.78% (very satisfied), the responsive element of 91.81% (very satisfied), the assurance aspect of 98.44% (very satisfied), the empathy aspect of 91.68% (very satisfied), and the tangible aspect of 85.85% (very satisfied). Based on the results of the research that has been conducted, it was concluded that patient satisfaction in all aspects, namely 90.11%, is included in the very satisfied category.